2021
DOI: 10.3389/fpsyt.2021.746276
|View full text |Cite|
|
Sign up to set email alerts
|

Genetic Predisposition Between COVID-19 and Four Mental Illnesses: A Bidirectional, Two-Sample Mendelian Randomization Study

Abstract: Background: The outbreak of 2019 coronavirus disease (COVID-19) has become a global pandemic. Although it has long been suspected that COVID-19 could contribute to the development of mental illness, and individuals with a pre-existing mental illness may have a higher risk of and poorer outcomes from COVID-19 infection, no evidence has established a causal association between them thus far.Methods: To investigate associations in support of a causal association between the severity of COVID-19 and mental illness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 40 publications
1
24
0
Order By: Relevance
“…Two-tailed p < 0.05 was used in all statistical tests. Bonferroni-corrected analysis was used with a threshold of p < 0.006 (a = 0.05/9 outcomes) ( Liu et al., 2021 ). Associations with p-values between 0.006 and 0.05 were considered suggestive evidence of causal associations, requiring further confirmation ( Liu et al., 2021 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two-tailed p < 0.05 was used in all statistical tests. Bonferroni-corrected analysis was used with a threshold of p < 0.006 (a = 0.05/9 outcomes) ( Liu et al., 2021 ). Associations with p-values between 0.006 and 0.05 were considered suggestive evidence of causal associations, requiring further confirmation ( Liu et al., 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…Bonferroni-corrected analysis was used with a threshold of p < 0.006 (a = 0.05/9 outcomes) ( Liu et al., 2021 ). Associations with p-values between 0.006 and 0.05 were considered suggestive evidence of causal associations, requiring further confirmation ( Liu et al., 2021 ). All statistical analyses were finished with the R version 4.0.3, TwoSampleMR version 0.5.5, and MRPRESSO version 1.0 ( Verbanck et al., 2018 ; Broadbent et al., 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…The primary analysis was inverse variance weighted (IVW) MR under a random-effect model, which assumed all genetic variants as valid instruments. Weighted median and MR-Egger methods were also performed [ 14 , 15 ]. The weighted median method can reveal consistent estimates even if up to 50% of the weight in the MR analysis comes from invalid genetic variants [ 16 ].…”
Section: Methodsmentioning
confidence: 99%
“…Perception of COVID-19 (P-COVID-19) was measured by a valid and reliable scale. The scale consists of seven items and two sub-dimensions: "dangerousness" and "contagiousness" and is in a five-point Likert structure, The expressions are evaluated as "I strongly disagree (1), " "I do not agree (2), " "I am undecided (3), " "I agree (4), " "I strongly agree (5)." Sub-dimension of dangerousness covers perceptions and beliefs about the danger posed by COVID-19.…”
Section: Covid-disease Perception Scalementioning
confidence: 99%
“…ADHD was associated with a significantly higher rate of hospitalization and being symptomatic ( 4 ). A systematic review and a meta-analysis demonstrated that ADHD patients have increased susceptibility and severity compared to controls ( 5 ). However, a recent longitudinal study that investigated pre-pandemic and pandemic data on neurodevelopmental conditions did not show strong evidence of differences in the distribution of infections in those with ADHD compared to those without ( 6 ).…”
Section: Introductionmentioning
confidence: 99%